Self-disclosure and its relationship to electronic extortion among university students (Journal of the College of Basic Education, 2024)
The current research aims to identify self-disclosure among university students, and to identify electronic blackmail among university students, to identify the relationship between self-disclosure and electronic extortion among university students, and the researcher relied on a descriptive approach to study the correlations to find out the relationship between the research variables, self-disclosure and electronic extortion. It is one of the most used approaches in this field, and the research community consists of female students of Al-Mustansiriya University for morning and evening studies for the academic year (2020-2021) with a total number of (18453) students. 200) female students, distributed among the faculties of the university, and for the purpose of completing the procedures, the researcher adopted the scale (Dhiab, 2005) to measure the concept of self-disclosure, which consists of 60 items, and the researcher adopted the scale (Al-Samarrai, 2021) in defining the concept of electronic extortion based on the theory of space transmission of Jaishankar, The scale may consist of 20 situations and two alternatives, and after the statistical treatments represented by using the statistical bag (SPSS), the research reached the following results: the first goal is a decrease in self-disclosure among female students, and the second goal is a high level of electronic extortion among female students, and the third goal is a correlation relationship There is a direct correlation between self-disclosure and electronic blackmail, and accordingly the researcher presented a set of recommendations and proposals, the most important of which are: the necessity of conducting training courses and workshops by psychological counseling units in colleges on technical guidance to train students in general and female students in particular to use communication sites in a safe and useful way them and avoid them falling victim to electronic extortion.